2014
DOI: 10.1371/journal.pone.0087653
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stressful Life Events on Excessive Alcohol Consumption in the French Population: Findings from the GAZEL Cohort Study

Abstract: BackgroundMajor life changes may play a causative role in health through lifestyle factors, such as alcohol. The objective was to examine the impact of stressful life events on heavy alcohol consumption among French adults.MethodsTrajectories of excessive alcohol consumption in 20,625 employees of the French national gas and electricity company for up to 5 years before and 5 years after an event, with annual measurements from 1992. We used repeated measures analysis of time series data indexed to events, emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 49 publications
2
50
0
3
Order By: Relevance
“…While many variables contribute to the development of alcohol use disorder (AUD), exposure to stressful life events represents a significant risk factor (Keyes et al, 2012). Stress increases alcohol consumption in alcohol dependent and non-dependent populations (Ayer et al, 2011; Tamers et al, 2014; Thomas et al, 2011), and stress is thought to underlie a transition to pathological drug use (Koob and Le Moal, 2005). Animal studies have revealed interactions between stress and ethanol self-administration under certain stressor and drinking paradigms, but some results have been equivocal (Becker et al, 2011; Noori et al, 2014; Spanagel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While many variables contribute to the development of alcohol use disorder (AUD), exposure to stressful life events represents a significant risk factor (Keyes et al, 2012). Stress increases alcohol consumption in alcohol dependent and non-dependent populations (Ayer et al, 2011; Tamers et al, 2014; Thomas et al, 2011), and stress is thought to underlie a transition to pathological drug use (Koob and Le Moal, 2005). Animal studies have revealed interactions between stress and ethanol self-administration under certain stressor and drinking paradigms, but some results have been equivocal (Becker et al, 2011; Noori et al, 2014; Spanagel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, some events may put the patient at risk in the period following hospital discharge. Evidence from cohort studies in the general population indicates that some major life events, including those that affect the individual's family, social, or professional life, influence excessive alcohol drinking among men and women; however, this effect is not necessarily permanent (Tamers et al., ; Yaogo et al., ; Zins et al., ). For individuals with alcohol dependence, life events such as divorce or separation might be associated with relapse (Pilowsky et al., ) and shorter time to death (Lewis et al., ).…”
mentioning
confidence: 99%
“…Since the data in this study were repeated measurement data from the same respondents throughout the 7-year follow-up period, the authors used regression models with the generalized estimating equation (GEE) method [38]. The GEE is a statistical approach generally used in the analysis of longitudinal data or repeated measurements [39][40][41][42][43][44], with the primary advantage being that it accounts for the within-adults variation [45]. Firstly, we used a linear regression model with GEE to assess the association between the food consumption score and the CES-D score.…”
Section: Resultsmentioning
confidence: 99%